When ni- and -nibud’ are logically equivalent: Evidence from Russian nominalizations - A. Gerasimova (Rhema. Рема, 2020)
This paper deals with the two sets of polarity sensitive items in Russian: ni- and -nibud’ pronouns. Non-specific indefinite -nibud’ pronouns (NSIs) are possible only in propositions that do not ensure truth, i.e. non-veridical contexts. Although clause-mate negation creates such a context, NSIs are incompatible with it and are substituted by negative ni- pronouns that are licensed only by negative concord. The incompatibility of NSIs with negation can be resolved in subjunctive sentences and embedded purpose čtoby-clauses, however, the licensing conditions in these cases are not defined. In this paper I introduce another context which licenses both types of pronouns, namely, negated process nominalizations. I determine the licensing conditions for the two types of pronouns in nominalization, and test previous approaches against the new data. In particular, I argue that -nibud’ pronouns are licensed in the scope of the nonveridical operator that is introduced in the main clause.